Molecular phylogeny of the Sceloporus torquatus species-group (Squamata: Phrynosomatidae) - Martínez-Méndez, Norberto; la Cruz, Fausto R. Méndez-De (Zootaxa, 2007)
The genus Sceloporus is one of the largest genus of lizards in North and Central America, with 22 species groups. Among these, the torquatus group has a notably wide geographic distribution with populations occurring from southern United States to Guatemala. In spite of the taxonomical work done with the group, some problems remain unsolved. We therefore obtained the phylogeny of the torquatus group, based on 925 bp of the ribosomal 16S gene, 912 bp of the ribosomal 12S gene, and 893 bp of the ND4 gene, for a total of 54 specimens of 25 taxa. The genes were analyzed, both separately and combined, by means of maximum parsimony and Bayesian inference analyses. The subspecies of S. serrifer did not form a monophyletic group. The sequence data refuted the morphological evidence that suggested that S. s. plioporus and S. cyanogenys are closely related to S. s. serrifer and to S. s. prezygus. Regardless, these last two were recovered as sister taxa. Moreover, evidence was found that S. ornatus does not form a monophyletic group, and that S. ornatus ornatus and S. oberon are a single species, despite their marked differences in coloration and scutelation. In addition, the non-monophyly of S. mucronatus was confirmed and the phylogenetic relationships of its different species were determined. At the same time, the subspecies of S. dugesii were recovered as a monophyletic group, refuting the nonmonophyly of this taxon suggested in the phylogenetic hypothesis of the entire genus.